Treatment success at the stage of obturation of root canal system - T. N. Manak; K. G. Kluiko; V. A. Mitronin (Эндодонтия Today, 2020)
Relevance. In the most cases periapical pathology is caused by intra-canal infections and its initial treatment is by conventional endodontic treatment. Endodontic failure is usually associated with technical limitations that prevent adequate intra – canal microbial control in the complex microanatomy of the root canal system. Even after the endodontic retreatment, owing to the factors of complex internal microanatomy, the failure may persist. In these clinical situations, apical microsurgery has been proven to be alternative for the clinical treatment of these infections. Various technological advances in the area of apical microsurgery have occurred in recent years. It is very important to obtain apical seal. With this purpose mineral trioxide aggregate (MTA) are widely used in dentistry.Aim. To evaluate and compare the fill density of mineral trioxide aggregate (MTA) produced by mechanical and manual mixing as well as the effect of sonic and ultrasonic (indirect activation) agitation during placement.Materials and methods. There were 30 acrylic transparent blocks with 30 -degree curved canals (Dentsply) used. All blocks were pre-weighted to the nearest 0,1 mg using a digital electronic balance (Model CPA225D-0CE, Sartorius, Gottingen, Germany) and then instrumented using Wave •OnePrimary 025.08 (Ni-Ti) rotary file (Dentsply) on the working length 16 mm. During instrumentation each canal was irrigated with 1 ml of water. Upon completion of instrumentation, the canal was dried with paper point. Each instumented block was weighted again. All blocks were randomly divided into 6 groups (with 5 specimens in each group) and obturated with different techniques with MTA which was also prepared by mechanical and manual mixing: 1st group – MTA manual mixing and insertion into the canal using N-Ti plugger; 2nd – manual mixing and sonic condensation, 3rd – mechanical mixing and manual insertion with a plugger, 4th – mechanical mixing and sonic condensation (2 s), 5th – manual mixing and sonic condensation (2 s), 6th – manual mixing and indirect ultrasonic condensation (2 s). In our experiment we used belarussian MTA (Rootseal, Belarus). After MTA setting all blocks were weighted. We used the weight of the MTA as an indicator of fill density because the formula for density is: Density = Mass/Volume.Results. Mechanical mixing of MTA and its sonic condensation during 2 s resulted in a greater fill density than that achieved using manual mixing and conventional insertion (with Ni-Ti plugger).Conclusions. Although manual mixing and conventional insertion of MTA are usually used by dentists, these techniques were not associated with a significant advantage in term of fill density over mechanical mixing and sonic condensation during short period of time (2 s).